2021
DOI: 10.38032/jea.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Plant Disease Detection through the Implementation of Diversified and Modified Neural Network Algorithms

Abstract: In the era of artificial systems, disease detection is becoming easier. For detecting disease, monitoring the plants 24 hours, visiting the agricultural office, or asking for help from a specialist seem difficult. This situation demands a user-friendly plant disease detection system, which allows people to detect whether the plant is diseased or not in an easier way.  If the plant is diseased, a treatment plan will also be notified. In this way, people can easily save time, money, and, most importantly, plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The suggested model performs better than the most complex deep learning models with less parameters. F. Nihar et al [33] employed numerous NN Algorithms, including other algorithms, and created a novel updated neural network architecture that produced 97.69% accuracy. M. Sardogan et al [34] to analyze and categorize tomato leaf disease, they have suggested a CNN and LVQ algorithm-based technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The suggested model performs better than the most complex deep learning models with less parameters. F. Nihar et al [33] employed numerous NN Algorithms, including other algorithms, and created a novel updated neural network architecture that produced 97.69% accuracy. M. Sardogan et al [34] to analyze and categorize tomato leaf disease, they have suggested a CNN and LVQ algorithm-based technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nihar et al [28] suggested a neural network-based system for detecting plant disease that will aid in the development of the agricultural system which can properly determine whether a plant is infected or healthy and has a 97.7% accuracy. This technology enables the user to detect diseases faster allowing them to take acceptable precautionary steps and save crops.…”
Section: Related Workmentioning
confidence: 99%